Trends of incidence, mortality and survival for chronic lymphocytic leukaemia / small lymphocytic lymphoma in Switzerland between 1997 and 2016: a population-based study (Swiss Medical Weekly, 2021)
BACKGROUNDDuring the last 20 years, treatment for chronic lymphocytic leukaemia (CLL) / small lymphocytic lymphoma (SLL) has advanced, with improved clinical outcomes in randomised controlled trials. Currently, no data have been published from Switzerland to assess effectiveness of recent healthcare advances in CLL/SLL on a population-based level. We aimed to estimate trends in incidence, mortality and survival for patients with CLL/SLL in Switzerland.METHODSWe retrospectively studied registry data from the National Agency for Cancer Registration (NACR) database in Switzerland from 1997 to 2016. We investigated incidence, mortality and survival in consecutive 5-year periods. Age-specific rates were calculated for three age groups (